The Radical Change in Migration Policies: from Letting Live to Letting Die (from Biopolitics to More and More Thanatopolitics) - Palidda, Salvatore (2021)
The text describes the salient aspects of the current world situation. Through a synthetic analysis of the process that led to the triumph of globalized liberalism, it is shown how starting in 1990 the war on migration is inscribed in a real thanatopolitics (letting die). In fact, the dominant people designate migration as the enemy of the 21st century because they fear that the increase in the world population is uncontrollable and that it overlaps with climate change causing - according to them - destabilizing invasions of migrants in rich countries. In reality, they fear that there is a need for an egalitarian redistribution of world wealth that could allow the decent survival of over 10 billion humans also on the condition of eliminating all sources of destruction on the planet and above all gas, uranium and rare earths.